AN ANALYSIS OF POLITENESS PRINCIPLE IN BADUNG REGENT CANDIDATES DEBATE IN 2015 - aryasih, made (Jurnal Pendidikan Bahasa Inggris Indonesia, 2020)
Abstract This study aimed at: 1) finding maxims of politeness principle expressed in Badung Regent Candidates Debate in 2015; 2) finding the most dominant maxim of politeness principle used in Badung Regent Candidates Debate in 2015. This study was designed mainly as a descriptive qualitative study which then supported by some descriptive quantification. The objects of the study were the utterances containing maxims of politeness principle expressed by the regent and vice regent candidates of Badung in Badung Regent Candidates Debate in 2015. The data were analyzed based on the theory of politeness principle proposed by Leech and the theory of categorization of speech act by Searle. The results of the study display that there are six maxims of politeness principle expressed in Badung Regent Candidates Debate in 2015, namely the tact maxim, the generosity maxim, the approbation maxim, the modest maxim, the agreement maxim and the sympathy maxim. Furthermore, it is found out that the generosity maxim is the most dominant maxim used by the regent and vice regent candidates in Badung Regent Candidates Debate in 2015. The generosity maxim expressed in the debate applied the commissive type of speech act. Through the utterances of this maxim, they intend to convince the audience that they attempt to minimize benefit to self and maximize cost to self. The maxims expressed by the regent and vice regent candidates in the debate have a goal to communicate effectively